IsoCaRB: A novel bioreactor system to characterize the lability and natural carbon isotopic (C-14, C-13) signatures of microbially respired organic matter - Beaupré, Steven R.; Mahmoudi, Nagissa; Pearson, Ann (LIMNOLOGY AND OCEANOGRAPHY-METHODS, 2016)
Organic matter is the dominant pool of reduced carbon in marine and freshwater systems. Mineralization of organic matter is largely attributed to complex and diverse microbial communities that mediate degradation and ultimately yield the terminal respiratory product, carbon dioxide (CO2). The factors that constrain the lability and degradation of organic matter remain unclear, but they involve a complex interplay between structural and chemical properties of the compounds, physical properties of the matrices, and the functional potential of the microorganisms that are present. To investigate these relationships, we developed a novel bioreactor system-called Isotopic Carbon Respirometer-Bioreactor (IsoCaRB)-that permits real-time monitoring of microbial CO2 production rates and collects sequential samples of this CO2 for off-line isotopic analyses (C-13, C-14). Application of this system to organic-rich sediments from Salt Pond, MA reveals that organic matter is oxidized both abiotically and microbially, and that the pattern of microbial respiration by the native sediment community is complex, accessing different carbon substrates over the course of incubation. Isotopic measurements show modern organic matter of progressively older ages (<= ca. 50 yr) is consumed, and this material has variable origins (salt marsh grasses, terrestrial, and marine organic matter). Collectively, the IsoCaRB system provides coupled insights into the sources, ages, and inherent biological and abiotic reactivity of natural organic matter.